Kritik Sastra Pendekatan Mimetik pada Lirik Lagu Wakaf Keikhlasan Karya Rafli Kande - Dahliana Dahliana (BADAN PENERBIT STIEPARI PRESS, 2025)
The aim of this research is to analyze how the lyrics of the song Waqf Keikhlasan by Rafli Kande represent social realities and events that have occurred using a mimetic approach. This approach views literary works as artificial or imitation of reality. This research uses a qualitative descriptive method with literature study data collection techniques. The data analysis technique is descriptive analysis. Descriptive data analysis is used to explain and organize data systematically to increase the researcher's understanding of the problem to be researched and present it as a finding.